Enhancing the Fibrinolytic Activity in Human Blood by Occlusion of Blood Vessels - Amery, A; Vermylen, J; Maes, H; Verstraete, M (Thrombosis and Haemostasis, 1962)
The lytic activity was measured in blood obtained from a superficial elbow vein when a cuff with a known pressure was attached above the elbow and compared with the activity in the blood taken at the same moment from the control arm without any pressure.1. Using a pressure 20 mm above the systolic pressure, no enhancement could be obtained in the first 10 minutes.2. Using a diastolic or systolic pressure during 3 minutes, the fibrinolytic activity was about 2.8 times the activity in the control sample.3. Using a pressure halfway the diastolic and systolic, the fibrinolytic activity after 3 minutes was about 3.5 times, and after 10 minutes about 11 times the activity in the control sample.